2023
DOI: 10.21931/rb/css/2023.08.01.70
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Spraying with Micro-Elements, Gibberellic Acid and Salicylic Acid on Some Yield Traits of Date Palm CV. Khastawi.

Nafea. A. Jubair,
Ahmed F. Z. Al-Dulaimy

Abstract: The study was conducted in one of the private palm orchards in the Euphrates district on date palm trees (CV. Khastawi) aged 30 years to find out the response of the date palm cultivar Khastawi to spraying with micro-elements at concentrations (0, 1 g L-1 ) and symbolized by (M0 and M1), and spraying with gibberellic acid at concentrations (0, 100, 200 mg L-1 ) and symbolized by (G0, G1, and G2) respectively, and spraying with salicylic acid in concentrations (0, 100, 200 mg L-1 ) and symbols symbolized by (S0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
0
0
Order By: Relevance
“…It also plays a crucial role in membrane stability and cell integrity. Increased leakage of low molecular weight solutes has been observed from plant tissue cells suffering from severe calcium deficiency, contributing to the collapse of cell membranes and loss of cell division activity [40][41][42]. [43] demonstrated that calcium treatment inhibits chlorophyll loss and increases leaf content.…”
Section: Manganese (Mg Kg -1 )mentioning
confidence: 99%
“…It also plays a crucial role in membrane stability and cell integrity. Increased leakage of low molecular weight solutes has been observed from plant tissue cells suffering from severe calcium deficiency, contributing to the collapse of cell membranes and loss of cell division activity [40][41][42]. [43] demonstrated that calcium treatment inhibits chlorophyll loss and increases leaf content.…”
Section: Manganese (Mg Kg -1 )mentioning
confidence: 99%
“…Hormones also contribute to increasing the content of carbohydrates, proline, and organic acids. These substances are known to be osmotic regulators, as well as antioxidants for free radicals resulting from salt stress [76,77,78]. Hormones also work to overcome the harmful effects of salinity by activating the synthesis of chlorophyll and inhibiting the breakdown of photosynthetic pigments.…”
Section: Role Of Some Growth Regulators In Overcoming the Harmful Eff...mentioning
confidence: 99%
“…In natural soil processes, nitrogen levels are augmented through microbiological activities, where nitrogen-fixing bacteria facilitate the oxidation of ammonium to nitrite, further transforming it into nitrate [10,11.12,13]. Sulfur is a vital element that, in conjunction with nitrogen, plays a crucial role in the synthesis of amino acids, proteins, amino nucleic acids, and nucleotides, essential components for various biological processes in plants [14,15,16]. The researcher [17] elucidated that the application of NPK fertilizer at varying concentrations (25,75, and 100 g per kg) to Ficus carica plants resulted in notable effects on various growth parameters.…”
Section: Introductionmentioning
confidence: 99%